2016
DOI: 10.1111/bjh.14071
|View full text |Cite
|
Sign up to set email alerts
|

18F‐FDG PETCT and trephine biopsy assessment of bone marrow involvement in lymphoma

Abstract: The ability of positron emission tomography-computerized tomography (PET-CT) to accurately detect bone marrow involvement (BMI) has been suggested in Hodgkin lymphoma (HL) and diffuse large B-cell lymphoma (DLBCL), but its abilities in other histologies is less established. The aim of this retrospective study was to confirm the role of PET-CT in detecting BMI in DLBCL and HL, and to explore its usefulness in other subtypes. Of the 149 newly diagnosed patients, common subtypes included DLBCL, follicular lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…In the setting of B-NHL, and particularly in the DLBCL category, the use of PET/CT and/or BMB for staging purposes is presently one of the most debated issues as different strategies have been proposed according to the divergent results of a number of distinct series or metaanalysis [3][4][5][6][7][8][12][13][14][15], or experience-based recommendations from experts in the field [4,5,[16][17][18][19][20]. With an endeavor to avoid susceptibility and collinearity biases in our study design, we show here the superiority of BMB over PET/CT in predicting PFS in a homogeneously-treated cohort of 203 DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of B-NHL, and particularly in the DLBCL category, the use of PET/CT and/or BMB for staging purposes is presently one of the most debated issues as different strategies have been proposed according to the divergent results of a number of distinct series or metaanalysis [3][4][5][6][7][8][12][13][14][15], or experience-based recommendations from experts in the field [4,5,[16][17][18][19][20]. With an endeavor to avoid susceptibility and collinearity biases in our study design, we show here the superiority of BMB over PET/CT in predicting PFS in a homogeneously-treated cohort of 203 DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study done on 38 patients with newly diagnosed diffuse large B‐cell lymphoma and negative blind BMB, showed that disease relapse or progression and death occurred more frequently in WB‐MRI positive patients than in WB‐MRI negative patients, suggesting that WB‐MRI findings may have relevant prognostic implications . Other studies have demonstrated that BMB does not change prognosis and treatment with respect to FDG‐PET/CT, in patients with HL and diffuse large B‐cell lymphoma, so FDG‐PET/CT may replace BMB for the assessment of BMI in these patients …”
Section: Discussionmentioning
confidence: 99%
“…Marginal zone and mantle cell lymphomas, even if they carry a higher risk of BMI, were under‐represented sub‐populations in our study. Second, the reference standard was BMB, the results of which are subjects to sampling errors, especially if BMI is focal or outside the pelvis . However, WB‐MRI and FDG‐PET/CT scans performed after therapy were also reviewed, and bone lesions were considered as the locations of disease when disappearing in posttreatment examinations.…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT has become more frequently utilized in detecting lymphomatous bone marrow involvement. In contrast to bone marrow biopsy, the noninvasive procedure enables the assessment of the entire marrow cavity while concurrently evaluating the extra-medullary disease [7].…”
Section: Introductionmentioning
confidence: 99%